ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP EFFECTIVE TAX RATE PADA PERUSAHAAN WHOLESALE AND RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
This study aims to determine Size, Profitability, Leverage, Capital Intensity Ratio, Inventory Intensity and Independent Commissioner of Effective Tax Rate Wholesale and Retail Trade companies listed on the Indonesia Stock Exchange. Population in this study are Wholesale and Retail companies listed on the Indonesia Stock Exchange. Sampling methods using purposive sampling period from 2010 to 2013. Tools of analysis used Multiple Regression Analysis to explain the related between variabels influence. The results showed that Size have negative not significant , Profitability have negative significant , Leverage have negative significant, Capital Intensity Ratio have negative significant, Inventory Intensity have positive significant, and Independent Commissioner have positif not significant to Effective Tax Rate. Keywords: Size, Profitability, Leverage, Capital Intensity Ratio, Inventory Inensity,  Independent Commissioner and Effective Tax Rate